Cytotoxic and genotoxic effects of environmental relevant concentrations of bisphenol A and interactions with doxorubicin - Ramos, Carina (2018)
Bisphenol A (BPA) is one of the most widely utilized endocrine disruptors to which humans are exposed, particularity through ingestion. BPA is an aneugenic compound with a putative association to tumorigenesis. Although extensively studied in estrogen-responsive cells, information regarding its effects on cells from the upper gastrointestinal tract exposed to free/active forms of BPA are still scarce. Similarly, BPA interactions with other drugs has been neglected, although it has been suggested to has a potential role in doxorubicin (DOX) chemoresistance. This study is intended to assess potential cytotoxic and genotoxic effects of BPA, as well as its interactions with DOX, in Human epithelial type 2 cells (Hep-2) originated from a human laryngeal carcinoma and in a DNA damage responsive cell line, the human lung fibroblasts (MRC-5). Cell viability was analyzed through the resazurin assay. The G protein-coupled estrogen receptor 1 (GPER) expression was visualized by immunodetection. Genotoxicity, namely DNA damage and oxidative DNA damage, were assessed by comet assay and micronuclei induction, and mitotic disruption was evaluated cytologically by fluorescent microscopy wif DAPI staining. Cytotoxicity analysis showed that exposure to BPA per se does not affect cellular viability. Nevertheless, the genotoxic analysis showed that BPA induced an increase of DNA damage in the Hep-2 cell line and in oxidative damage in the MRC-5 cell line. An increase of micronuclei was also observed in both cell lines following BPA exposure. BPA and DOX co-exposures suggested that BPA acts as an antagonist of DOX effects in both cell lines. The interaction wif DOX appears to be cell type dependent, exhibiting a non-monotonic response curve in MRC-5 cells, a GPER expressing cell line. Our study emphasizes the need for a deeper knowledge of BPA interactions, particularly with chemotherapeutic agents, in the context of risk assessment and public health.